Effect of Palliative Care Application in Spiritual Dimension according to Multicultural Ways on Knowledge and Spiritual Care Competencies among Village Health Volunteers in Narathiwat Province - Dereh, Nurdeenee; A-lee, Ansory; Adulyarat, Manasavee; หวังสวัสดิ์, ธิดารัตน์ (Nursing Journal of The Ministry of Public Health, 2021)
This quasi-experimental study with one group pretest-posttest design aimed to compare the knowledge and spiritual ability scores before and after using an application of spiritual dimension caring according to multicultural way among village health volunteers and to examine the level of satisfaction with the application. The sample consisted of 45 village health volunteers selected through multistage random sampling. The research instruments were divided into 2 parts: 1) the application of spiritual dimension in a multicultural way "I CARE" 2) the data collected consisted of: demographic data, spiritual care knowledge questionnaire, spiritual skills questionnaire, and application satisfaction evaluation form. The data were analyzed using descriptive statistics and a paired t-test. The results of this study showed that the mean scores for knowledge and spiritual skills after participating in the program were significantly higher than the scores before participating in the program at a p level of .001 (t = -9.23, t = -33.59, respectively). The overall satisfaction score was at a high level.